MECHANICAL SUBMENTAL LIPOSUCTION - Elyzabeth De Queiroz Carneiro, Dayanny; Belém Rodrigues Barros Soares, Vinícius; Gomes Moreira, Andréia (Health and Society, 2022)
The standard of beauty has been one of the most incessant aesthetic quests by thousands of people regardless of sex, race, gender and social status. According to research institutes, more than 70% of Brazilians want to perform some facial correction. This report searched the literature for knowledge of facial aesthetics and orofacial harmonization in relation to the neck area, an area that greatly bothers people because it is closely related to the age factor and the impression of youth. The neck will play a crucial role in the aesthetics of the overall appearance. With that as facial measurements as well as angle between jaw and neck, between 90 and 110 degrees, resulting in structures, and attractive. Considering the importance of mechanical double chin liposuction in orofacial harmonization and as it is an area of expertise of the dental surgeon, we proposed to evaluate the literature and clinically and photographically the indicative signs of harmonization before and after mechanical double chin liposuction. Based on the liposuction analyzed, it was possible that the recommendation is effective and well performed.